2020
DOI: 10.1021/acs.jpcb.0c03163
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Structures of DNA Minidumbbells Comprising Type II Tetraloops with a Purine Minor Groove Residue

Abstract: Minidumbbell (MDB) is a newly discovered DNA structure formed by native sequences, which serves as a possible structural intermediate causing repeat expansion mutations in the genome and also a functional structural motif in constructing DNA-based molecular switches. Until now, all the reported MDBs containing two adjacent type II tetraloops were formed by pyrimidine-rich sequences 5′-YYYR YYYR-3′ (Y and R represent pyrimidine and purine, respectively), wherein the second and sixth residues folded into the min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Six additional sequences, namely 5ʹ‐CTTTG CGTTG‐3ʹ, 5ʹ‐CTTTG CATTG‐3ʹ, 5ʹ‐CTTTG CTGTG‐3ʹ, 5ʹ‐CTTTG CTATG‐3ʹ, 5ʹ‐CTTTG CTTGG‐3ʹ and 5ʹ‐CTTTG CTTAG‐3ʹ which contained a L2ʹ, L3ʹ and L4ʹ purine (G or A), respectively, were designed. In a recent study on MDBs containing two tetraloops, it was found that a purine residue in the 5ʹ‐tetraloop favoured the formation of dimeric conformers [21]. Therefore, sequences containing a L2, L3 or L4 purine in the 5ʹ‐pentaloop were not designed in this work.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six additional sequences, namely 5ʹ‐CTTTG CGTTG‐3ʹ, 5ʹ‐CTTTG CATTG‐3ʹ, 5ʹ‐CTTTG CTGTG‐3ʹ, 5ʹ‐CTTTG CTATG‐3ʹ, 5ʹ‐CTTTG CTTGG‐3ʹ and 5ʹ‐CTTTG CTTAG‐3ʹ which contained a L2ʹ, L3ʹ and L4ʹ purine (G or A), respectively, were designed. In a recent study on MDBs containing two tetraloops, it was found that a purine residue in the 5ʹ‐tetraloop favoured the formation of dimeric conformers [21]. Therefore, sequences containing a L2, L3 or L4 purine in the 5ʹ‐pentaloop were not designed in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have found that replacement of a pyrimidine with a purine in MDBs containing two tetraloops lead to formation of a dimeric species under a high ionic concentration [21]. Accordingly, the solution structures of the above‐mentioned MDBs were characterized under a low ionic strength condition, that is 10 m m NaPi at neutral pH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations